2019
DOI: 10.1088/1755-1315/380/1/012016
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of allelochemical compounds signature in two mangrove forest species of Rhizophora apiculata and Acrostichum aureum and potential in suppressing weed growth

Abstract: Rhizophora apiculata and Acrostichum aureum are a common mangrove species in Malaysia. Allelochemical interaction of the mangrove species was speculated to play an important role in dominance in the harsh mangrove environment. This study assessed the quantitative and qualitative determination for total phenolic content and individual phenolic compounds as allelochemical content for R. apiculata and A. aureum leaves as a potential allelopathic substance. The second objective is to investigate the allelopathic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…Little is known about the allelopathic potential of mangrove species: Chen & Peng [ 30 ] tested the allelopathic potential of three mangrove species on model target plants and another study suggested that allelopathic processes could be involved in mangrove succession [ 31 ]. To date, only a few studies have reported the allelopathic potential of mangroves species in weed management [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about the allelopathic potential of mangrove species: Chen & Peng [ 30 ] tested the allelopathic potential of three mangrove species on model target plants and another study suggested that allelopathic processes could be involved in mangrove succession [ 31 ]. To date, only a few studies have reported the allelopathic potential of mangroves species in weed management [ 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of growth by allelopathic effects from mangrove phytochemicals has been reported for crops (Desai et al, 2016), weeds (Dhaou et al, 2022;Othman et al, 2019), wetland plants (Lang et al, 2021), microalgae (Sun et al, 2012), and other mangrove species (Wang et al, 2009). However, there is currently no scientific evidence indicating that naturally released mangrove leaf phytochemicals can reduce pathogen load in seawater, leaving this as an open question.…”
Section: Box 72 Mangrove Phytochemicals and Their Potential Antimicro...mentioning
confidence: 99%